Delay of Near-relativistic Electrons with Respect to Type III Radio Bursts throughout the Inner Heliosphere - J. G. Mitchell; E. R. Christian; G. A. de Nolfo; C. M. S. Cohen; M. E. Hill; A. Kouloumvakos; A. W. Labrador; R. A. Leske; D. J. McComas; R. L. McNutt Jr.; D. G. Mitchell; M. Shen; et al. (The Astrophysical Journal)
Energetic electrons accelerated by solar eruptive events are frequently observed to have inferred injection times that appear significantly delayed with respect to electromagnetic emission including type III radio bursts. This is noteworthy because type III radio emission is produced by streaming suprathermal electrons, and thus this observed delay implies either a delayed injection/release of higher-energy electrons, compared with the suprathermal population, and/or a delay of the electrons observed in situ in transit through the interplanetary medium. A number of studies have investigated these delays with spacecraft located at 1 au. In this study, we examine energetic electron onsets and type III radio bursts observed by the Integrated Science Investigation of the Sun (IS⊙IS) and the FIELDS Radio Frequency Spectrometer instrument on Parker Solar Probe at a variety of heliocentric distances. With these observations, we can uniquely decouple the effects of acceleration and transport and shed light on the source of these delays. We present a survey of electron events observed by IS⊙IS within the first ∼6 yr of the mission, including their delays with respect to type III emission between ∼0.1 and 0.8 au. These results suggest that energetic electron delays with respect to type III radio bursts are not purely produced by a delayed injection/release as has been suggested, implying that transport processes play a role.